PENGARUH PEMBERIAN BAWANG MERAH TERHADAP PENURUNAN PANAS PADA BALITA DI KLINIK PRATAMA BERTHA PASAR IV MABAR HILIR TAHUN 2023 - Siregar, Gf Gustina; Purba, Tetty Junita; Wahyuni, Eka Sri; Wahyuni, Rizky (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
hyperthermia > 37.5. The thermal effect of shallots is based on the utilization of thermal energy through conduction and evaporation, or insulation from other objects through direct contact. The aim is to carry out midwifery care by providing intervention and observation by applying the red onion technique to reducing heat in toddlers at the Pratama Bertha Pasar IV Mabar Hilir clinic in 2023. There This is a pre-treatment test and a post-treatment test that can be more accurately identified and compared to the pre-treatment test. This research activity aims to determine sthe effect of giving crushed shallots To lower the body temperature of a febrile infant. Result is, 15 respondents after being given the Crush of Shallots, most of the Toddlers experienced a decrease in body temperature, namely as many as 13 respondents (86.7%).Conclusion: This can be seen from the research results as many as 15 toddlers with fever before being given shallots had an average increase in heat of 15 respondents (100) while after being given shallots experienced an average increase in temperature of 2 respondents (1.13) Keywords: Shallots, Toddlers, Fever